O Impacto Traumático de Experiências de Vergonha: Estudo das propriedades psicométricas da versão portuguesa da Impact of Event Scale - Revised - Matos, Marcela (2011)
Early shame experiences have been perceived as possible traumatic experiences, functioning as traumatic memories with an impact on the vulnerability to psychopathology. The current study explores the psychometric properties of the portuguese version of the Impact of Event Scale-Revised (IES-R; Weiss & Marmar, 1997) in a normal population sample of 811 subjects. Construct validity was analysed through Principal Components Analysis. Results support the one dimensional structure, underlying IES-R, explaining 55.4% of the variance. We found item-total correlations ranging from moderate to high (>.56) and a high internal consistency (α=.96), suggesting an excellent reliability of the scale. Convergent and divergent validity was confirmed by the high correlations found with CES and by the moderate correlations with DASS Depression, Anxiety and Stress. The portuguese version of the IES-R seems to be a reliable and valid measure of traumatic stress reactions, namely intrusion, avoidance and hyperarousal, in relation to shame experiences.